Western Perspectives on the Mediterranean : Cultural Transfer in Late Antiquity and the Early Middle Ages, 400-800 AD - Fischer, Andreas (Criminal Practice Ser, 2014)
Cover -- Half-title -- Title -- Copyright -- Contents -- Preface -- List of Contributors -- Introduction -- 1 The Burgundians and Byzantium -- 2 'Avenger of all Perjury' in Constantinople, Ravenna and Metz: Saint Polyeuctus, Sigibert I, and the Division of Charibert's Kingdom in 568 -- 1. Gregory of Tours and the Church of Saint Polyeuctus in Constantinople -- 2. Polyeuctus, Hilary and Martin - A Saintly Triumvirate in Merovingian Politics -- 3. The Division of Charibert's Kingdom -- 4. Saint Polyeuctus and Metz, the Austrasian Capital -- 5. The Division of Charibert's Kingdom and the Political Situation in 568 -- 6. Conclusion -- 3 The Historian as Cultural Broker in the Late and Post-Roman West -- 4 Rewriting History: Fredegar's Perspectives on the Mediterranean -- 1. The Fredegar-Chronicle: Horizon and Structure -- 2. Fredegar and the Mediterranean: Questions and Problems -- 3. Sources and Channels of Communication -- 4. Making History: Author, Narrator and the Appropriation of Motifs -- 5. A Tangible Context? Constans II in Italy, Abbot Hadrian, and Fredegar -- 6. Conclusions -- 5 Greek Popes: Yes or No, and Did It Matter? -- 6 Mediterranean Lessons for Northumbrian Monks in Bede's Chronica Maiora -- Notes -- Bibliography -- Index.